Penggunaan Dosimeter Film,OSL,Dioda, dan Ion Chamber dalam Verifikasi Dosis pada Teknik Modulated Arc Therapy (VMAT) - Pina, Felita Agri; Maulida, Friska Tsania; Setiawan, Kevin Aditya; Putri, Erlinda Ratnasari (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2024)
The Modulated Arc Therapy (VMAT) technique is an advanced radiotherapy method that allows more optimal radiation dose distribution in a shorter radiation time. Several types of dosimeters that are often used for this verification include film dosimeters, OSL (Optically Stimulated Luminescence), diodes, and ion chambers, each of which has advantages and disadvantages. This review was conducted to compare the use of various dosimeters in dose verification using the VMAT technique, with a focus on the advantages and disadvantages of each tool. This research is based on a literature study of 15 articles. The literature study was carried out for 2 months. The article is limited to a discussion of environmental influences on air quality. The articles used were taken from 2015 to 2023. The results of this study show that although all types of dosimeters have advantages, selecting the right dosimeter is very dependent on the specific needs in dose verification on VMAT. Diodes, ion chambers, OSLs, and films perform well in appropriate application contexts, but each has limitations in terms of accuracy, sensitivity, and measurement time. The articles discussed show that OSL and film are more effective in dose measurements in three-dimensional distribution, while diodes and ion chambers are more appropriate for point dose measurements.